Development of a Parent-Oriented Module for Optimizing Independence in Early Childhood - Awanda Erna; Azizah Amal; Muhammad Yusri Bachtiar; Herlina Herlina; Hasmawaty Hasmawaty (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
The development of early childhood independence requires active parental involvement supported by structured and practical guidance that can be applied in everyday home environments. This study aims to develop a parent-oriented module to optimize early childhood independence and to examine its feasibility and effectiveness in improving parents’ understanding. This research employed a Research and Development approach involving stages of needs analysis, product design, development, validation, and field testing. Data were collected through interviews, questionnaires, observations, and pre-test and post-test assessments. The results of the needs analysis indicate that parents require practical and structured guidance to support children’s independence at home. The developed module was validated by experts and categorized as valid with minor revisions. User responses in both small- and large-scale trials show that the module is highly acceptable and feasible for independent use by parents. Furthermore, the effectiveness test reveals a significant improvement in parents’ understanding, as indicated by an increase in the mean score from 52.00 in the pre-test to 80.75 in the post-test, supported by statistical analysis showing a significant difference (p < 0.05). These findings indicate that the module is effective as a practical learning resource that enhances parental involvement and supports the development of early childhood independence.